An investigation on the use of snus and its association with respiratory and sleep-related symptoms: a cross-sectional population study. Issue 5 (29th May 2017) - Gudnadóttir, Arna Ýr; Ólafsdóttir, Inga Sif; Middelveld, Roelinde; Ekerljung, Linda; Forsberg, Bertil; Franklin, Karl; Lindberg, Eva; Janson, Christer
Abstract : Introduction: Studies of the health effects of moist oral tobacco, snus, have produced inconsistent results. The main objective of this study is to examine the health effects of snus use on asthma, respiratory symptoms and sleep-related problems, a field that has not been investigated before. Methods and material: This cross-sectional study was based on a postal questionnaire completed by 26 697 (59.3%) participants aged 16 to 75 years and living in Sweden. The questionnaire included questions on tobacco use, asthma, respiratory symptoms and sleeping problems. The association of snus use with asthma, respiratory symptoms and sleep-related symptoms was mainly tested in never-smokers (n=16 082). Results: The current use of snus in never-smokers was associated with an increased risk of asthma (OR 1.51 (95% CI 1.28 to 1.77)), asthmatic symptoms, chronic bronchitis and chronic rhinosinusitis. This association was not present among ex-snus users. Snoring was independently related to both the former and current use of snus ((OR 1.37 (95% CI 1.12 to 1.68)) and (OR 1.59 (95% CI 1.34 to 1.89), respectively)). A higher risk of difficulty inducing sleep was seen among snus users. Conclusion: Snus use was associated with a higher prevalence of asthma, respiratory symptoms and snoring. Healthcare professionals should be aware of these possible adverse effects of snus use.